Advances in Continuous Glucose Monitoring: Clinical Applications - Kwon, So Yoon; Moon, Jun Sung (Endocrinology and metabolism (Seoul), 2025)
Continuous glucose monitoring (CGM) has revolutionized diabetes management, significantly enhancing glycemic control across diverse patient populations. Recent evidence supports its effectiveness in both type 1 and type 2 diabetes management, with benefits extending beyond traditional glucose monitoring approaches. CGM has demonstrated substantial improvements in glycemic control across multiple metrics. Studies report consistent glycosylated hemoglobin reductions of 0.25%–3.0% and notable time in range improvements of 15%–34%. CGM effectively reduces hypoglycemic events, with studies reporting significant reductions in time spent in hypoglycemia. CGM also serves as an educational tool for lifestyle modification, providing real-time feedback that helps patients understand how diet and physical activity affect glucose levels. While skin-related complications remain a concern, technological advancements have addressed many initial concerns. High satisfaction rates and long-term use suggest that device-related issues are manageable with proper education and support. Despite high initial costs, CGM’s prevention of complications and hospitalizations ultimately reduces healthcare expenditures. With appropriate training and support, CGM represents a transformative technology for comprehensive diabetes care.